2012
DOI: 10.1111/j.1542-4758.2012.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass index and aortic arch calcification score are independent mortality predictors of maintenance hemodialysis patients

Abstract: To analyze predictive factors for all‐cause mortality, cardiovascular (CV) mortality, nonfatal CV events (CVE) in maintenance hemodialysis (MHD) patients, and to compare the effects of standard hemodialysis (HD) and online hemodiafiltration (HDF) on these factors and outcomes. A total of 333 MHD patients were prospectively followed up for 50 ± 15 months and all‐cause death, CV death and CVE were registered. At the baseline, demographic, clinical, and laboratory data of the whole population were recorded. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In our analyses, LVM was not indexed for body surface area or divided by height 2.7 , as was done in analogous studies (22,25,26). A downside of ratios is that an observed relation may be due to changes in the nominator, the denominator, or both.…”
Section: Echocardiography Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analyses, LVM was not indexed for body surface area or divided by height 2.7 , as was done in analogous studies (22,25,26). A downside of ratios is that an observed relation may be due to changes in the nominator, the denominator, or both.…”
Section: Echocardiography Measurementsmentioning
confidence: 99%
“…In two observational studies comparing HDF and HD performed in 118 patients (HDF, n=58) and 333 patients (HDF, n=65), LVM index decreased in the HDF group and remained stable in the HD group over a follow-up period of 2 and 4 years, respectively (25,26). However, nonrandomized studies are prone to confounding by indication: It cannot be ruled out that patients with a more favorable prognosis were allocated to HDF.…”
Section: Effect Of Hdf On Lvm Ef and Pwvmentioning
confidence: 99%
“…However, high convection volumes (>18.8 L) was not related to change of left ventricular mass and EF . Liu et al performed online HDF using high‐flux polysulphone membranes with 14.4 L/session convection volume . Schiffl et al used post‐dilution online HDF with volumes of 18.0‐22.5 L per session .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of studies included in the analysis was relatively small and only two studies were prospective, randomized, controlled trials. The length of follow‐up of measurements was extremely heterogeneous with a range of 3 months to 4 years …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liu et al [26] reported that the LVMI was an independent mortality predictor of maintenance HD patients. According to another previous study, increased LVEDD was an independent predictor of all-cause mortality [27].…”
Section: Discussionmentioning
confidence: 99%